The adsorption of oppositely charged polyelectrolyte/surfactant mixtures: Neutron reflection from dodecyl trimethylammonium bromide and sodium poly(styrene sulfonate) at the air/water interface - Taylor, D; Thomas, R; Penfold, J (2002)
The interactions between the cationic surfactant dodecyl trimethylammonium bromide (C 12TAB) and the anionic polymer sodium poly(styrene sulfonate) (NaPSS) have been studied using surface tension and tron reflectivity techniques. Neutron reflection shows that the surface consists of a mixture of polymer and surfactant over surfactant concentrations ranging from twice the critical micelle concentration (CMC) to 1/100 of the CMC for polymer concentrations between 20 and 140 ppm. In the lower surfactant concentration range the amount of surfactant adsorbed approximately corresponds to a surfactant monolayer (area per molecule ∼ 50 Å 2), but at a higher concentration this increases to an amount approximately corresponding to three adsorbed layers (area per molecule = 17 Å 2). A similar increase is observed in the amount of adsorbed polyelectrolyte. The jump in the adsorbed amounts is accompanied by an increase in the overall thickness of the adsorbed layer from 20 Å to about 60 Å. Based on fits to the neutron reflectivity data from different isotopic compositions the structure of the higher concentration layer is a sandwich structure with an outer surfactant layer and a submerged micellar layer or defective bilayer. This composite layer may be associated with adsorption of the polymer/micelle complex at the interface.